Why Cancer Cells Crave Sugar: A Review: Mengapa Sel Kanker Sangat Membutuhkan Gula: Sebuah Ulasan - Sadiq, Dina H. (Universitas Muhammadiyah Sidoarjo, 2025)
In addition to causing weight gain, eating too much sugar raises the risk of obesity and diabetes, both of which raise the chance of cancer. It turns out that while eating sugar does not always cause cancer, it can cause the disease because of the way it affects your waist. Sugar is necessary for cancer cells to survive, not to proliferate and divide. Although this sugar is absorbed by all bodily tissues, it is more readily absorbed by tissues with higher energy requirements, such as cancer cells. Because of this, some people have concluded that sugar accelerates the growth of cancer cells.